The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1186/s12864-022-08781-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation in Pacific oyster reproductive tissue in response to ocean acidification

Abstract: Background There is a need to investigate mechanisms of phenotypic plasticity in marine invertebrates as negative effects of climate change, like ocean acidification, are experienced by coastal ecosystems. Environmentally-induced changes to the methylome may regulate gene expression, but methylome responses can be species- and tissue-specific. Tissue-specificity has implications for gonad tissue, as gonad-specific methylation patterns may be inherited by offspring. We used the Pacific oyster (C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…Previous studies have also shown that DNA methylation in the body wall and intestinal tissues of A. japonicus mainly occurred at the CpG sites during Vibrio splendens infestation, aestivation, and heat stress (Sun et al, 2020;Yang et al, 2020;Wen et al, 2021). In addition, the DNA methylation pattern in A. japonicus was consistent with research results on the Pacific abalone, Yesso scallop, Pacific oyster (Huang et al, 2021;Yuan et al, 2021;Venkataraman et al, 2022), and other metazoans (Lechner et al, 2013). Although CpG was the main type of DNA methylation, there were some differences in the characteristics of CpG in different regions of the genome.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have also shown that DNA methylation in the body wall and intestinal tissues of A. japonicus mainly occurred at the CpG sites during Vibrio splendens infestation, aestivation, and heat stress (Sun et al, 2020;Yang et al, 2020;Wen et al, 2021). In addition, the DNA methylation pattern in A. japonicus was consistent with research results on the Pacific abalone, Yesso scallop, Pacific oyster (Huang et al, 2021;Yuan et al, 2021;Venkataraman et al, 2022), and other metazoans (Lechner et al, 2013). Although CpG was the main type of DNA methylation, there were some differences in the characteristics of CpG in different regions of the genome.…”
Section: Discussionsupporting
confidence: 88%
“…If organisms experience low pH during reproductive conditioning, environmental cues may be integrated in the germline through DNA methylation and other epigenetic modifications (Bell and Hellmann, 2019). Sex-associated methylation differences have been documented in C. gigas, and OA exposure modified the reproductive tissue methylome in C. gigas and C. virginica (Venkataraman et al, 2020;Sun et al, 2022;Venkataraman et al, 2022). Changes to DNA methylation due to low pH may impact successful reproduction or explain intergenerational effects of these conditions on marine invertebrates.…”
Section: Understand Limitations Of Intergenerational Studiesmentioning
confidence: 99%
“…When examining partial pressures of CO 2 , it was found that exposure to elevated levels caused proteins associated with the cytoskeleton, such as actin isoforms, and oxidative stress to be upregulated (Tomanek et al, 2011). Analysis of gonad methylomes in Pacific oysters also showed genes associated with protein ubiquitination to be differentially methylated in response to differing pH levels (Venkataraman et al, 2022). Here, we found that glutathione S-transferase was upregulated in GA and MA at 20°C, and higher activity of this protein has been found in M. edulis extracted from sites with high pollution (Fitzpatrick et al, 1997), which can alter pH levels.…”
Section: Discussionmentioning
confidence: 99%